2010
DOI: 10.1101/gad.1920310
|View full text |Cite
|
Sign up to set email alerts
|

Myc protein is stabilized by suppression of a novel E3 ligase complex in cancer cells

Abstract: Rapid Myc protein turnover is critical for maintaining basal levels of Myc activity in normal cells and a prompt response to changing growth signals. We characterize a new Myc-interacting factor, TRPC4AP (transient receptor potential cation channel, subfamily C, member 4-associated protein)/TRUSS (tumor necrosis factor receptor-associated ubiquitous scaffolding and signaling protein), which is the receptor for a DDB1 (damage-specific DNA-binding protein 1)–CUL4 (Cullin 4) E3 ligase complex for selective Myc de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 26 publications
2
96
0
1
Order By: Relevance
“…20 Several E3 ligases, including FBW7, SKP2, TRUSS, HectH9, β-Trcp1 and Hsc70-interacting protein (CHIP), have been identified as responsible for c-Myc degradation. 19,[22][23][24][25][26][27][28] However, it is still unclear whether c-Myc stability is regulated by ubiquitin-independent pathways. In the present study, we demonstrated that proteasome activator REGγ is a novel negative regulator of c-Myc and provided evidence that this regulation is evolutionarily conserved.…”
mentioning
confidence: 99%
“…20 Several E3 ligases, including FBW7, SKP2, TRUSS, HectH9, β-Trcp1 and Hsc70-interacting protein (CHIP), have been identified as responsible for c-Myc degradation. 19,[22][23][24][25][26][27][28] However, it is still unclear whether c-Myc stability is regulated by ubiquitin-independent pathways. In the present study, we demonstrated that proteasome activator REGγ is a novel negative regulator of c-Myc and provided evidence that this regulation is evolutionarily conserved.…”
mentioning
confidence: 99%
“…As we observed that overexpression of Skp2 down-regulated TRUSS levels and an earlier report suggested low levels of TRUSS in a number of human cancer cell lines, 12 we next investigated the pattern of TRUSS and Skp2 protein expression in different tumor tissues. Serial sections of different human tumors (one each of HCC, pancreatic adenocarcinoma, colonic adenocarcinoma and breast invasive ductal carcinoma) and their adjacent non-cancerous tissues (ANCT) prepared from the paraffin blocks, were analyzed by immunohistochemistry (IHC) using specific antibodies.…”
Section: Elevated Expression Of Skp2 Correlates With Low Expression Omentioning
confidence: 91%
“…12 Considering the importance of c-Myc in cell cycle regulation, we analyzed the expression of TRUSS in the synchronized population of human hepatoma Huh-7 cells (Fig. S1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations